A model of the market for bank credit: The case of Germany - Peter Bofinger; Daniel Maas; Mathias Ries (University of Würzburg, Department of Economics, 2017)
Since the financial crisis there exists a widespread discussion about the role of banking in a monetary economy. We contribute to this discussion by presenting a basic model of the banking sector which models banks as originators of credit without owning pre-collected savings or reserves beforehand. Additionally, we estimate an empirical model of the German credit market for non-financial corporations in a disequilibrium framework. Empirically, we detect a significant role for the variables that are chosen on the basis of our price-theoretic model.
Keywords: E51; 330; Credit; Money Supply; Money Multiplier